Quality-Shaping Factors and Endodontic Treatment amongst General Dental Practitioners with a Focus on Denmark - Sune Demant; Merete Markvart; Lars Bjørndal (International Journal of Dentistry)
There is a gap between the endodontic outcome that can be achieved and the outcome observed on the basis of worldwide general dental practitioner data. The quality of root canal treatment (RCT) is shaped by the dentist's knowledge, attitude, and skills, but it may also be influenced by the patient's demands and degree of satisfaction. The topic has only been sparsely investigated. Although dental health has increased over the years in Denmark, the number of performed root fillings has also increased, probably because the number of tooth extractions have declined and more molar teeth have been treated. Caries appears to be the main cause for performing RCT and a preventive approach by employing stepwise excavation may reduce RCT, but this strategy does not remove the gap. Factors influencing RCT quality could be the status on adoption of nickel-titanium rotary technology, more focus on infection control (rubber dam use, knowledge of factors important for prognosis), as dentists often think that they are good at doing RCT, but often perform inadequately, an alteration of clinician's awareness of their performance in the context of dental practices, seems warranted. Finally, the development of new preventive modalities for pulp and apical inflammation are crucial.